Investigating the Effects of Retro Walking on Pain, Physical Function, and Flexibility in Chronic Non-specific Low Back Pain - Tahreem Raza; Saima Riaz; Faraz Ahmad; Iqra Shehzadi; Nimra Ijaz; Sidra Ali (Iranian Rehabilitation Journal, 2023)
Objectives: Chronic non-specific low back pain (CNSLBP) is described as pain whose pathoanatomical cause cannot be determined. The current study aims to evaluate the impact of retro-walking on pain, flexibility, and physical functions in patients with CNSLBP. Methods: A randomized controlled trial was conducted in the Physical Therapy Department of District Head Quarter Hospital Nankana Sahib, Punjab, Pakistan from September 2021 to March 2022. The trial was conducted on 36 patients, randomly divided into 2 groups of 18 patients. Conventional treatment and retro-walking were given to the experimental group and the conventional treatment alone was provided to the control group for 1 month with 3 sessions per week. The outcome variables were pain, the flexibility of hamstrings and lumbar region, and physical function assessed by numeric pain rating scale, sit and reach test, modified Schober test, and modified Oswestry disability index, respectively. The data were assessed at pre-treatment after the sixth and twelfth sessions. Results: This study showed a significant difference in the numeric pain rating scale, sit-and-reach test, and modified Oswestry disability index with a P<0.05 in both groups after intervention. However, in the group comparison, these variables showed better results in the retro-walking group compared to others with a P<0.001 after both the sixth and twelfth sessions. Discussion: The current study suggested that when added up to conventional treatment, retro-walking was more beneficial in reducing pain and enhancing the flexibility and physical function in patients with CNSLBP when compared to conventional treatment alone; therefore, it should be added to the treatment protocol for chronic non-specific pain in the lower back.